2016
DOI: 10.1101/sqb.2016.81.030874
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Synthesis Is a Metabolic Liability of Non–Small Cell Lung Cancer

Abstract: The renaissance in the study of cancer metabolism has refocused efforts to identify and target metabolic dependencies of tumors as an approach for cancer therapy. One of the unique metabolic requirements that cancer cells possess to sustain their biosynthetic growth demands is altered fatty acid metabolism, in particular the synthesis of de novo fatty acids that are required as cellular building blocks to support cell division. Enhanced fatty acid synthesis that is observed in many tumor types has been postula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 71 publications
(83 reference statements)
0
29
1
Order By: Relevance
“…Lipid metabolism is also involved in NSCLC development. Studies showed that lipid synthesis is the metabolic liability of lipid metabolism in NSCLC (41). Different from normal tissue, NSCLC shows an enhanced lipid synthesis ability to favor its lipid demand due to rapid cell proliferation.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Lipid metabolism is also involved in NSCLC development. Studies showed that lipid synthesis is the metabolic liability of lipid metabolism in NSCLC (41). Different from normal tissue, NSCLC shows an enhanced lipid synthesis ability to favor its lipid demand due to rapid cell proliferation.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…ACC1 is a kind of lipid metabolism enzyme and converts from acetyl CoA to malonyl CoA which is the rate limiting step in de novo fatty acid synthesis (FASyn) [20]. Lots of cancers demonstrate an increase in FASyn and decrease of FASyn inhibits the tumor growth [21,22]. It is observed an overexpression of ACC1 in several kinks of cancers, including breast cancer, lung cancer and prostate cancer [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that one of the common colonization sites for metastatic lung cancer is liver (33)(34)(35)(36), pointing to a favorable environment for cancer cells to thrive, we wondered whether the four urinary metabolite biomarkers may be able to distinguish liver cancer cases from high-risk patients (e.g., harboring HBV and HCV infections)-individuals who would be subject to liver cancer screening. While the two cancer types share some of the mutual metabolic characteristics, such as deregulated lipid metabolism (23,37,38), not enough is known about the similarities between lung and liver cancer metabolism or about overlapping products of metabolism that may serve as robust biomarkers in both cancer types. We therefore hypothesized that the four metabolites previously described as robust markers of lung cancer (27), even 2 or more years prior to diagnosis (26), may demonstrate a significant diagnostic and prognostic potential in liver cancer.…”
Section: Discussionmentioning
confidence: 99%